Cancer survivorship: an integral part of Europe's research agenda. Issue 3 (8th January 2019) - Lagergren, Pernilla; Schandl, Anna; Aaronson, Neil K.; Adami, Hans‐Olov; de Lorenzo, Francesco; Denis, Louis; Faithfull, Sara; Liu, Lifang; Meunier, Franḉoise; Ulrich, Cornelia; ,
Abstract : Cancer survivorship has traditionally received little prioritisation and attention. For a long time, the treatment of cancer has been the main focus of healthcare providers' efforts. It is time to increase the amount of attention given to patients' long‐term well‐being and their ability to return to a productive and good life. This article describes the current state of knowledge and identifies research areas in need of development to enable interventions for improved survivorship for all cancer patients in Europe. The article is summed up with 11 points in need of further focus. Abstract : Cancer survivorship has traditionally received little attention. It is time to increase the amount of attention given to patients' long‐term well‐being and their ability to return to a productive and good life. This article describes the current state of knowledge and identifies research areas in need of development to enable interventions for improved survivorship for all cancer patients in Europe.